Results from Colombia's 2016 report card on physical activity for children and youth (2016)
Background: Physical activity (PA) is vital to the holistic development of young people. Regular participation in PA is associated with substantial benefits for health, cognitive function, and social inclusion. Recognizing the potential of PA in the context of the current peace process in Colombia, the purpose of this article is to present the methodology and results of Colombia's second Report Card on PA for children and youth. Methods: A group of experts on PA graded 14 PA indicators based on data from national surveys and policy documents. Results: National and departmental policy indicators received a grade of B, while organized sport participation, overweight, obesity, community influence, and nongovernment initiatives indicators received a grade of C. Overall PA levels, active transportation, sedentary behaviors, and school influence received a grade of D. Active play, low physical fitness, and family influence received an Incomplete grade. Conclusion: PA levels are low and sedentary behaviors are high in Colombian children and youth, with notable geographic differences. A broad policy framework translated into specific actions could provide unique opportunities to bridge the gap between knowledge and practice, and contribute to social integration goals in a postconflict setting. © 2016 Human Kinetics, Inc.